Range prediction for the Giant Fruit-Eating Bat, Artibeus amplus (Phyllostomidae: Stenodermatinae) in South America - Ramoni-Perazzi, Paolo (2012)
Suitable habitat range for Artibeus amplus in the Neotropics was predicted using maximum entropy niche modeling, environmental covariates, and museum records from 61 locations across Colombia, Venezuela, Guyana, and Suriname. Environmental covariates included (a) bioclimatic data; (b) elevation; (c) geology; and (d) soil. Model selection was based on graphic analyses of omission/commission, and Akaike information criterion (AIC), small sample size corrected AIC (AICc) and Bayesian information criterion (BIC). Models incorporating all of the above covariates performed best. The predicted suitable habitat range adjusted well to the known range of A. amplus. However, our analysis identifies northern Brazil as a spot requiring further research to determine the presence of A. amplus.